Recontextualizing cybertextual discourse with post-functional linguistics and mindful deep-learning - Rahardi, R. Kunjana (Universitas Ahmad Dahlan, 2025)
This study explores the conceptualization of linguistic context as cybertextual, a multimodal and digitally mediated construct within the framework of post-functional linguistics. It argues that digital communication extends linguistic boundaries, integrating visual, gestural, aural, spatial, and textual modes in meaning-making. Anchored in mindful deep learning, mindfulness is viewed not only as cognitive awareness but as a pedagogical stance that nurtures attentiveness, emotional regulation, and reflective engagement with multimodal semiotic resources. The study aims to (1) classify diverse forms of cybertextual context and (2) interpret their functional identities through mindful learning. Using a qualitative descriptive approach, it analyzes authentic data from Instagram to examine meaning construction through semiotic layering. Employing extralinguistic equivalence analysis, the research identifies five interrelated modalities—visual, gestural, aural, spatial, and linguistic—each contributing distinctively to interactional meaning. The integration of mindful deep learning within this model reveals how learners can cultivate semiotic sensitivity, interpretive accuracy, and empathetic communication in digital environments. The study advances post-functional linguistic theory and provides pedagogical insights for fostering critical and ethical language awareness in multimodal, digitally enriched learning settings.